L'égalité selon la Déclaration canadienne et la Charte québécoise : réflexions à partir de la nouvelle Loi sur les jurés ou la Charte des droits québécoise : un régime d'exception? - Grenier, Bernard (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1977)
Quebec has a charter of Human Rights and Freedoms, which came into force by proclamation, on June 28th 1976. Yet, afresh Jurors Act was assented to barely two days later which contained a clause that a number of enumerated sections have effect notwithstanding the Charter. The concern there was clearly the right to equality, which is enshrined in some sections of the Charter. This article purports to assess the proper and specific meaning of equality within the context of the Quebec Charter, and in the light of the case law surrounding the Canadian Bill of Rights. The enactment of a non obstante clause into the Jurors Act has been, in our view, both unnecessary and inappropriate.